Antibody‐induced vascular inflammation skews infiltrating macrophages to a novel remodeling phenotype in a model of transplant rejection. Issue 10 (22nd May 2020) - Wei, Xuedong; Valenzuela, Nicole M.; Rossetti, Maura; Sosa, Rebecca A.; Nevarez‐Mejia, Jessica; Fishbein, Gregory A.; Mulder, Arend; Dhar, Jayeeta; Keslar, Karen S.; Baldwin, William M.; Fairchild, Robert L.; Hou, Jianquan; et al.
Abstract : HLA donor‐specific antibodies (DSAs) binding to vascular endothelial cells of the allograft trigger inflammation, vessel injury, and antibody‐mediated rejection (AMR). Accumulation of intragraft‐recipient macrophages is a histological characteristic of AMR, which portends worse outcome. HLA class I (HLA I) DSAs enhance monocyte recruitment by activating endothelial cells and engaging FcγRs, but the DSA‐activated donor endothelial influence on macrophage differentiation is unknown. In this study, we explored the consequence of DSA‐activated endothelium on infiltrating monocyte differentiation. Here we show that cardiac allografts from murine recipients treated with MHC I DSA upregulated genes related to monocyte transmigration and Fc receptor stimulation. Human monocytes co‐cultured with HLA I IgG‐stimulated primary human endothelium promoted monocyte differentiation into CD68 + CD206 + CD163 + macrophages (M(HLA I IgG)), whereas HLA I F(ab′)2 stimulated endothelium solely induced higher CD206 (M(HLA I F(ab′)2 )). Both macrophage subtypes exhibited significant changes in discrete cytokines/chemokines and unique gene expression profiles. Cross‐comparison of gene transcripts between murine DSA‐treated cardiac allografts and human co‐cultured macrophages identified overlapping genes. These findings uncover the role of HLA I DSA‐activated endothelium in monocyte differentiation, and point to a novel, remodeling phenotype of infiltrating macrophages that may contribute to vascular injury. Abstract : The authors report that binding of HLA‐class I donor‐specific antibodies to vascular endothelial cells promotes monocyte differentiation into a unique phenotype of infiltrating macrophages that may contribute to vascular injury.